1965
DOI: 10.1002/cjce.5450430608
|View full text |Cite
|
Sign up to set email alerts
|

Combined free‐and‐forced convection: I. Heat transfer in aiding flow

Abstract: A study of the rate of heat transfer to air at low velocities was performed in a heated stainless tube, 4.42‐in. inside diameter and 102‐in. long. The air flowed upward through the tube, under which conditions the buoyancy forces aided the forced flow. The investigation covered a Reynolds number range from 385 to 4,930, and nominal wall temperatures of 100, 500 and 950°C. For laminar aiding flow, the local Nusselt number could be correlated with (NGr/NRc). For turbulent flow, the local Nusselt number was corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Aung and Worku [7,8] have presented the numerical analysis for both asymmetric wall temperature and asymmetric wall heat flux in a vertical channel and found the criteria for the occurrence of flow reversal. It has been found that in a vertical tube the aiding buoyancy force can enhance the heat transfer rate [9,10] while the opposing buoyancy force can reduce the heat transfer rate [ll]. However, Wirtz et.…”
Section: N O M E N C L a T U R Ementioning
confidence: 99%
“…Aung and Worku [7,8] have presented the numerical analysis for both asymmetric wall temperature and asymmetric wall heat flux in a vertical channel and found the criteria for the occurrence of flow reversal. It has been found that in a vertical tube the aiding buoyancy force can enhance the heat transfer rate [9,10] while the opposing buoyancy force can reduce the heat transfer rate [ll]. However, Wirtz et.…”
Section: N O M E N C L a T U R Ementioning
confidence: 99%
“…If we compare equation (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), we see that the differences occur Expressions for noncircular tubes are presented in a variety of sources (4-6). In many cases, it is possible to use the relation between equivalent diameter and Deq.…”
Section: Forced Convection Heat Transfer Coefficient Expressions For mentioning
confidence: 99%
“…In many cases, it is possible to use the relation between equivalent diameter and Deq. = 4Rh (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Exceptions are discussed in reference 6. One additional point should be made about the foregoing heat transfer equations.…”
Section: Forced Convection Heat Transfer Coefficient Expressions For mentioning
confidence: 99%
See 2 more Smart Citations